(untitled) (Journal of Information Technologies in Education (ITE), 2025)
The article studies the peculiarities of interaction of participants in the educational process in institutions of higher education (HEI) in the conditions of distance learning. It is determined that the introduction of distance learning radically changes the traditional approaches to communication between teachers, students and administration, putting forward new requirements for the organization of the educational process. The authors emphasize that effective interaction between participants in the educational process depends on the level of digital literacy, the quality of technical support and the adaptation of educational programs to the online environment. The work focuses on modern technologies and platforms used in distance learning, such as Zoom, Google Meet, Microsoft Teams and Moodle. The advantages of distance learning are analyzed, including the availability of educational resources, the possibility of personalizing the educational process and flexibility in the time and place of study. However, identified the main challenges facing the participants of the educational process. These are technical problems (unstable Internet connection, lack of appropriate equipment for students or teachers), insufficient level of digital competence of individual participants and lack of interactivity in online interaction. The author emphasizes that effective interaction in the conditions of distance learning should be based on the active use of modern educational technologies, providing two-way feedback and creating a favorable online environment. It is noted that the use of Web-technologies, cloud environments, platforms and information and communication technologies helps to increase the efficiency of the educational process, providing an individualized approach and stimulating the development of creative abilities of applicants for education. They increase the intensity and effectiveness of training, creating conditions for continuous professional development. This allows us to process a larger amount of information and contributes to the growth of information and communication competence of future specialists in the educational sector. The article offers recommendations for improving distance learning in HEI. Among them are the development of digital infrastructure, increasing the level of digital competence of teachers and students, improving distance learning methods. The need for regular monitoring of the quality of distance learning for its further improvement is noted. The results of the study emphasize the importance of an integrated approach to the organization of distance learning, which includes technical, pedagogical and psychological components, as well as active communication between all participants in the educational process.